Melaleuca quinquenervia, Melaleuca - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS, 2010)
FOR 257, a 3-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, and Heather V. Quintana, describes this non-native, invasive tree found in Louisiana and south of central Florida, where it invades a variety of habitat types ranging from wet swamps to dry uplands — scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.